Performance Modeling of File System Pairs in Hypervisor-Based Virtual Environment Applied on KVM Hypervisor Case Study - Đorđević, Borislav; Timočenko, Valentina; Bogdanoski, Mitko; Maček, Nemanja (Journal of Computer and Forensic Sciences, 2023)
This paper proposed an approach to mathematical modeling of the file system performance in a hypervisor-based virtual environment, with special focus on the file system pair interactions. The main goal of this research is to conduct an in-depth analysis of the filesystem pair behavior with respect to the performance costs originating from the employed technologies, such as H-Trees, B-Trees and Copy-on-Write/Overwrite update method, and different application workload types. The modeling provides a collection of hypotheses about the expected behavior. The modeling and the hypotheses are validated based on the results obtained for a specific case study. Our study reports on a file system performance comparison in the context of KVM hypervisor-based full hardware virtualization, application-level benchmarking, and 64-bit Linux filesystems Ext4, XFS, and Btrfs. The Filebench benchmark tool is applied for comprehensive testing of the filesystem performance under fair-play conditions. According to the obtained results, we provide a set of recommendations (i.e., a Knowledge Data Base) for optimal filesystem pair selection for the KVM hypervisor. Finally, it is important to note that the proposed modeling is also applicable to other hypervisor-based virtualizations.